13.7k views
0 votes
I PROMISE BRINLIEST THIS IS VERY EASY I JUST DON'T KNOW!!!!!!!!!! Simplify the polynomial

3x2 + 5x – 5x2 – 4x + 5 – 2

A.)–8x2 – 9x + 3
B.)2x2 + x + 3
C.)–2x2– 9x + 3
D.)–2x2 + x + 3

User Xtsoler
by
6.6k points

2 Answers

2 votes

Answer:

x-1

Explanation:

(3)(2)+5x-(5)(2)-4x+5-2

=6+5x-10-4x+5-2

=x-1

User Taytay
by
6.3k points
4 votes

Answer:

-2x2+x+3

Explanation:

you have to combine like terms

-5x2+ 3x2= -2x2

5x-(-4x)= x

5-2=3

-2x2+x+3

User Natig Babayev
by
5.7k points